2019
DOI: 10.1016/j.energy.2019.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Overview of ocean power technology

Abstract: This work discusses and provides a critical expose of some of the newly emerging renewable energy technologies with special concentration on marine energy generation. The work shows that there are several promising new developments in harvesting marine energy and it examines some of these technologies and discusses their advantages and some of the obstacles that are impeding the commercialisation of these emerging technologies. This includes wave energy harvesting, tidal energy harvesting, ocean thermal energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(53 citation statements)
references
References 47 publications
0
44
0
1
Order By: Relevance
“…The main challenges in developing MHK based energy are high investment and maintenance costs (e.g., hostile operating environment) and difficulty of integration their produced electricity to the electrical grid (e.g., remote areas and deep sea) [5], [6]. There are many approaches to address the high cost challenges, such as lower the cost of turbine design or optimized operational strategy [7], and this study focuses on maximizing the output power of an ocean current turbine (OCT).…”
Section: Introductionmentioning
confidence: 99%
“…The main challenges in developing MHK based energy are high investment and maintenance costs (e.g., hostile operating environment) and difficulty of integration their produced electricity to the electrical grid (e.g., remote areas and deep sea) [5], [6]. There are many approaches to address the high cost challenges, such as lower the cost of turbine design or optimized operational strategy [7], and this study focuses on maximizing the output power of an ocean current turbine (OCT).…”
Section: Introductionmentioning
confidence: 99%
“…Wave energy has the capacity to travel for long distances with low energy loss. For instance, the wind storm originated from the "Western Atlantic Ocean" have the capacity to travel toward the "Western Cost of Europe" with a very minimal loss of the energy [6,7]. It is revealed that the wave energy systems can produce up to 90% of the global energy demand.…”
Section: Introductionmentioning
confidence: 99%
“…Illustration of onshore, offshore and offshore categories for Wave Energy Systems (WES)[6] Kinds of Wave Energy Systems (WES)[6] …”
mentioning
confidence: 99%
“…The main challenges in developing MHK based energy are high investment and maintenance costs (e.g., hostile operating environment) and difficulty of integration their produced electricity to the electrical grid (e.g., remote areas and deep sea). There are many approaches to address the high cost challenges, such as lowering the cost of turbine design or optimizing the operational strategy [5], and this study focuses on maximizing the output power of an ocean current turbine (OCT).…”
Section: Introductionmentioning
confidence: 99%